Application of InSAR for Earth Surface Deformation Disaster Analysis - Bayuaji, Luhur (2014)
Interferometry Synthetic Aperture Radar (InSAR) is a radar technique used in remote sensing for earth observation. The technique utilizes the difference in the phase of waves returning to synthetic aperture radar (SAR) satellite. By using two SAR images, Digital Elevation Model (DEM) or map of surface deformation can be generated. It is also powerful tool for measuring earth surface deformation due to volcanic activity, earthquake, ground water migration and anthropogenic activity.